TEACHING VIDEO GAME TRANSLATION: FIRST STEPS, SYSTEMS AND HANDS-ON EXPERIENCE - Esqueda, Marileide Dias; Andrade Stupiello, Erika Nogueira de [UNESP] (Univ Fed Minas Gerais, Fac Letras, 2018)
Despite the significant growth of the game localization industry in the past years, translation undergraduate curricula in Brazil still lacks formal training in game localization, often leaving novice translators no alternative but to search for the required skills informally in game translation communities. Designing a video game localization course in translation undergraduate programs in public universities is a complex task in today's reality, particularly due to limited access to free and authentic materials. This paper describes a game localization teaching experience at the undergraduate level with special focus on how to handle the linguistic assets of the online race game SuperTuxKart, while trying to shed some light on potential translation requirements of entertainment software and its incorporation into translation programs.
Keywords: video game localization; video game translation; translator training; translation undergraduate program; SuperTuxKart